The Students' Resilience from The Broken Home Family at The High School of Kuantan Singingi District - Safar, Mulkismawati (International Journal of Applied Guidance and Counseling, 2022)
Multiple challenges with personal growth and development might arise in students from broken homes. This research aims to identify the student resilience from broken home families, as well as the experience and significance of the situation. This reserach used a mixed-method with embedded design. The total number of quantitative study respondents was 100, while the total number of qualitative informants was 10. Quantitative data retrieval strategies employ psychological scale and qualitative data using depth interviews. In general, student resilience falls under the category of average. The feature of optimism received the greatest score, while the aspect of reaching out received the lowest. To be able to survive in difficult situations, the informant tries to remain calm, controls inner impulses in various ways, believes that every problem has a solution, empathizes with others, believes in self-capability, analyzes the origins of problems, and searches for answers. The existence of mothers and younger siblings, as well as mindset and goals, contribute to the survivability (resilience) of informants in broken home families. Informants interpret their experience by taking wisdom and building expectations to be pious children, successful people, and proud parents by performing and working.